EFEKTIFITAS TEMULAWAK DALAM MENURUNKAN TEKANAN DARAH PADA LANSIA DI UPT PANTI SOSIAL TRESNA WERDHA MULIA DHARMA KABUPATEN KUBU RAYA - ., Dwi Tias Fitriani (ProNers, 2013)
Abstract Javanese Ginger is one Indonesian herbs that easily can be found and also widely used as a tradisionalmedicine. Efficacy of javanese ginger can help inhibit blood clotting, which can lower cholesterol levels canaffect blood pressure and javanese ginger also has the effect of one pharmacologically active substancegermakron which has anti-inflammatory effects and inhibiting edema (swelling). This study aimed todetermine the effect of  javanese ginger in decreased the blood pressure. After doing some research with thestudy design of pre-experimental one group pre test-post test in the absence of control groups with 12respondents were involved. They were 65-75 years old, there are differences in the number of malerespondents and female , which consisted of 7 men and 5 women, and 10 respondents who did not smoke.The result showed that the mean systolic blood pressure before intervention was 159,17 mmHg and the meansystolic blood presure after the intervention was 147,50 mmHg with an average difference 11,667 mmHg andp value 0,02. It can be concluded that there is a change in the value of systole before and after administrationof javanese ginger. To the average value of diastole before intervention was 95,83 mmHg and 88,33 mmHgafter intervention by the difference in average blood pressure of 7,500 mmHg and p value of  0,032. It can beseen that there is a change in diastolic values before and after administration of javanese ginger. So, javaneseginger is effective in lowering blood pressure and javanese ginger can be one alternative for lowering bloodpressure. Keyword : Javanese Ginger, Blood Pressure, Hipertency